Altered volcanic ash layers of the Late Cretaceous San Felipe Formation, Sierra Madre Oriental (Northeastern Mexico): U-Pb geochronology, provenance and tectonic setting - Velasco Tapia, Fernando; Martínez Paco, Margarita; Iriondo, Alexander; Ocampo Díaz, Yam Zul Ernesto; Cruz Gámez, Esther María; Ramos Ledezma, Andrés; Andaverde Arredondo, Jorge Alberto; Ostroumov, Mikhail; Masuch Oesterreich, Dirk (Dr. James Kellog, 2016)
A detailed petrographic, geochemical, and UePb geochronological study of altered volcanic ash layers, collected in eight outcrops of the Late Cretaceous San Felipe Formation (Sierra Madre Oriental, North- eastern Mexico), has been carried out. The main objectives have been: (1) to establish a deposit period, and (2) to propose a reliable provenance-transport-deposit-diagenetic model. These volcano- sedimentary strata represent the altered remains of vitreous-crystalline ash (main grains: quartz + K- feldspar (sanidine) + Na-plagioclase + zircon + biotite; groundmass: glass + calcite + clinochlore + illite) deposited and preserved in a shallow, relatively large in area, open platform environment. Major and trace element geochemistry indicate that parent volcanism was mainly rhyodacitic to rhyolitic in composition. Discrimination diagrams suggest a link to continental arc transitional to extension tectonic setting. UePb geochronology in zircon has revealed that the volcanic ash was released from their sources approximately during the range 84.6 ± 0.8 to 73.7 ± 0.3 Ma, being transported to the depocenters. Burial diagenesis process was marked by: (a) a limited recycling, (b) the partial loss of original components (mainly K-feldspar, plagioclase, biotite and glass), and (c) the addition of quartz, calcite, illite and cli- nochlore. The location of the source area remains uncertain, although the lack of enrichment in Zr/Sc ratio suggests that ashes were subjected to relatively fast and short-distance transport process. El Peñuelo intrusive complex, at 130-170 km west of the depocenters, is the nearest known zone of active magmatism during the Upper Cretaceous. This intermediate to felsic pluton, characterized by a geochemical affinity to post-orogenic tectonic setting, could be linked to the volcanic sources.